Adsorptive removal of toxic heavy metal and dyes from wastewater by rice husk (lignocellulosic biomass) derived activated biochar: A fixed-bed column adsorption study - Md. Mahmudur Rahman; Mohd. Maniruzzaman; Nor ealam; Parvej Mahmud; Sumiya Khatun; Md. Kaowsar Hossain; Md. Ismail Hossain; Md. Hasanuzzaman; Md. Ashraful Alam; Md. Al-amin; Bijoy Chandra Ghos (Carbohydrate Polymer Technologies and Applications)
Rapid industrialization/urbanization has been marked as a responsible factor for the creation of bulky effluent which is loaded with several harmful toxicants resulting in a hursh damage to the ecosystem and public safety/secuerity. To mitigate this crucial issue, here a fixed-bed column adsorption technology were chosen due to its simplecity, cost-effectivity, reuseablity. Meanwhile, multifunctional biosorbent i.e functionallized rice husk biochar (FRHBC) was produced by EIPS technique from a beneficial source namely rice(Oriza sativa) waste shell. The experiments were conducted to optimize the effect of influential factors like concentration, flowrates, and bed height. To observe the bulk properties the samples were characterized by FESEM,EDX,BET, FTIR-ATR,XRD, and TGA analysis. The effluents were investigated by AAS and UV–vis-NIR techniques. As per the findings it has been stated that the synthesized FRHBC adsorbents have possessed a promizing 2D honeycomb-like well-oriented mesoporous surface microstructure with a larger surface area around 36.84 m2/g. Additionally holds substantial active binding sites, lower crystallinity nearly 23±0.03%, and higher thermal stability upto 700 °C. Noteworthy that the maximum adsorption performence was found 179.77 and 173.01 mg/g for Pb2+ and MB dye. Hence, the newly produced multifunctional FRHBC bioadsorbents would be benificially used to purify real-time industrial wastewater for sustainable environmental protection.